"Idiopathic" intracranial hypertension: An update from neurointerventional research for clinicians. (April 2023) - Fargen, Kyle M; Coffman, Stephanie; Torosian, Taron; Brinjikji, Waleed; Nye, Barbara L; Hui, Ferdinand
Background: The recognition of venous sinus stenosis as a contributing factor in the majority of patients with idiopathic intracranial hypertension coupled with increasing cerebral venography and venous sinus stenting experience have dramatically improved our understanding of the pathophysiologic mechanisms driving this disease. There is now a dense, growing body of research in the neurointerventional literature detailing anatomical and physiological mechanisms of disease which has not been widely disseminated among clinicians. Methods: A literature search was conducted, covering the most recent neurointerventional literature on idiopathic intracranial hypertension, the pathophysiology of idiopathic intracranial hypertension, and management strategies (including venous sinus stenting), and subsequently summarized to provide a comprehensive review of the most recently published studies on idiopathic intracranial hypertension pathophysiology and management. Conclusion: Recent studies in the neurointerventional literature have greatly improved our understanding of the pathophysiologic mechanisms causing idiopathic intracranial hypertension and its associated conditions. The ability to make individualized, patient-specific treatment approaches has been made possible by advances in our understanding of how venous sinus stenosis and cerebral venous hypertension fundamentally contribute to idiopathic intracranial hypertension.